(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Rheumatoid arthritis (RA) is a chronic, systemic inflammatory disorder that primarily affects the small joints of hand. In the present study, hand grip strength was estimated on purposively selected 205 patients with RA aged 25-65 years. Correlations of handgrip strength have also been studied with some anthropometric and functional variables in patients with RA. Materials and methods: The subjects were assessed for handgrip strength (both dominant and non dominant), two functional variables, i.e. pain and pain today, and eight anthropometric variables namely, height, weight, BMI, hand and upper arm circumferences, forearm, upperarm and total arm length with standard techniques. Results: It was observed that the patients with RA had significantly lesser (p<0.001) handgrip strength than controls. It was also found that both younger and older patients had significantly lesser (p<0.001) handgrip strength than their control counterparts. Handgrip strength of patients with RA showed significant positive correlations with height and hand circumference, and significant negative correlations with pain today, forearm and upper arm length Conclusion: It might be concluded that handgrip strength had significant reduction in patients with RA as compared to controls. Moreover, handgrip strength had significant correlations with some functional and anthropometric variables.